The effect of DOACs on laboratory tests and their removal by activated carbon to limit interference in functional assays. (15th June 2020) - Exner, Thomas; Rigano, Joseph; Favaloro, Emmanuel J.
Abstract: We aimed to review the interfering effect of DOACs on tests for haemostatic function and then to discuss overcoming these with activated carbon (AC) products, thereby eliminating DOAC issues from test plasmas. Recent relevant articles were reviewed and are discussed. Laboratory tests for DOACs, lupus anticoagulant, factor assays and APC Resistance were carried out in such publications with and without an AC product on various instruments using reagents approved for diagnostic use in well‐regulated clinical laboratories. All reports on this plasma pre‐treatment by AC products agree that they extract DOACs from plasma samples with minimal effect on underlying clotting tests. The specific extraction of DOACs significantly reduced false positive lupus anticoagulant detection and provided more reliable results in clotting factor assays, APC resistance and other thrombophilia tests. Dabigatran and edoxaban seem to be adsorbed more thoroughly by AC from plasmas than rivaroxaban and apixaban. In summary, most of the AC products reviewed here appear to remove DOACs from test plasmas without significantly affecting underlying clotting tests and permit correct diagnosis of various haemostatic conditions despite the initial presence of DOACs. The application of such agents as a sample pre‐treatment to overcome the effects of DOACs for routine coagulation testing is supported by the emerging literature.